Wild articulations : environmentalism and Indigeneity in Northern Australia - Neale, Timothy (University of Hawaiʻi Press, 2017)
Since the nineteenth-century expeditions, Northern Australia has been both a fascination and concern to the administrators of settler governance in Australia. Neighboring Southeast Asia and Melanesia, its expansive and relatively undeveloped tropical savanna lands are alternately framed as a market opportunity, an ecological prize, a threat to national sovereignty, and a social welfare problem. Over the last several decades, while developers have eagerly promoted the mineral and agricultural potential of its monsoonal catchments, conservationists speak of these same sites as rare biodiverse habitats, and settler governments focus on the "social dysfunction" of its Indigenous communities. Meanwhile, across the north, Indigenous people themselves have sought to wrest greater equity in the management of their lives and the use of their country. In Wild Articulations, Neale examines environmentalism, Indigeneity, and development in Northern Australia through the recent controversy surrounding the Wild Rivers Act 2005 (Qld) in Cape York Peninsula, an event that drew together a diverse cast of actors--including traditional owners, prime ministers, politicians, environmentalists, mining companies, the late Steve Irwin, crocodiles, and river systems--to contest the future of the north. With a population of fewer than 18,000 people spread over a landmass of over 50,000 square miles, Cape York Peninsula remains a "frontier" in many senses. Long constructed as a wild space--whether as terra nullius, a zone of legal exception, or a biodiverse wilderness region in need of conservation--Australia's north has seen two fundamental political changes over the past two decades. The first is the legal recognition of Indigenous land rights, reaching over a majority of its area. The second is that the region has been the center of national debates regarding the market integration and social normalization of Indigenous people, attracting the attention of federal and state governments and becoming a site for intensive neoliberal reforms. Drawing connections with other settler colonial nations such as Canada and Aotearoa New Zealand, Wild Articulations examines how Indigenous lands continue to be imagined and governed as "wild."